Health-Related Fitness Profiles and Physical Activity Behavior in Elementary School Students - Fatoni; Juhanis, Juhanis; Iskandar, Iskandar; Raswadi, Mohammad Dika (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
Fitness and health are important indicators in supporting the growth and development of elementary school students. However, increasing sedentary lifestyles may negatively affect children’s physical activity and fitness levels. This study aimed to analyze the profile of health-related physical fitness and examine the relationship between physical activity behavior and fitness components among elementary school students. A descriptive-analytical method with a cross-sectional design was employed, involving 43 students from SD Inpres Karunrung. Physical fitness was assessed using a battery of tests measuring cardiorespiratory fitness, muscular strength and endurance, flexibility, and body composition, while physical activity behavior was measured using a physical activity questionnaire. Data were analyzed descriptively and correlationally using the Spearman rho test with SPSS version 25. The results showed that most students were classified in the moderate category across nearly all physical fitness components. A positive and significant relationship was found between physical activity and cardiorespiratory fitness (r = 0.462; p < 0.05) as well as muscular strength and endurance (r = 0.398; p < 0.05). No significant relationship was observed with flexibility and body composition. In conclusion, physical activity plays an important role in supporting health-related physical fitness, particularly functional fitness components, in elementary school students.